Making the achievement of zero hunger and malnutrition a priority: A critical assessment of recent national Zero Hunger Strategic Reviews from Asia and the Pacific - Benson, Todd (HEC Press, 2021)
Background and Objectives: Through Zero Hunger Strategic Reviews, national governments articulate how they can achieve the second Sustainable Development Goal targets of zero hunger and zero malnutrition by 2030. To suggest how such strategic reviews might accelerate progress towards those goals, an in-depth critical assessment was undertaken of Zero Hunger Strategic Reviews carried out between 2015 and 2019 in 13 countries in Asia and the Pacific. The appraisal focused on the conceptual frameworks used to guide the content of the processes and, secondly, on how well those involved understood the factors that drive or block change in their respective countries. Methods and Study Design: The qualitative study involved a desk review of: (1) all reports produced for the 13 strategic reviews; (2) guidance notes for their implementation; and (3) conceptual frameworks pertinent to them. Results: More explicit use of globally accepted conceptual frameworks would strengthen the national strategic reviews. More importantly, none considered closely the challenges that would arise as efforts are made to obtain approval for reforms and increased allocations of public resources to address hunger and malnutrition more effectively. Conclusions: Any recommendations from such strategic reviews will need to be assessed against competing development priorities and then planned, coordinated, and implemented effectively. While accurate technical understanding is necessary to take strategic action, the best plans to eliminate hunger and malnutrition will flounder if efforts are not also made to advocate for change, to build political leadership, and to hold accountable those responsible for the actions required.